From football to soccer : the early history of the beautiful game in the United States - Bunk, Brian D., 1968- (Sport and society., 2021)
"Across North America, native peoples and colonists alike played a variety of kicking games long before soccer's emergence in the late 1800s. Brian D. Bunk examines the development and social impact of these sports through the rise of professional soccer after World War I. As he shows, the various games called football gave women an outlet as athletes and encouraged men to form social bonds based on educational experience, occupation, ethnic identity, or military service. Football also followed young people to college as higher education expanded in the nineteenth century. University play, along with the arrival of immigrants from the British Isles, helped spark the creation of organized soccer in the United States-and the beautiful game's transformation into a truly international sport. A multilayered look at one game's place in American life, From Football to Soccer refutes the notion of the U.S. as a land outside of football history"--